Multi-model climate projections of the main cyclogenesis hot-spots and associated winds over the eastern coast of South America - de Jesus, Eduardo Marcos; da Rocha, Rosmeri Porfírio; Crespo, Natália Machado; Reboita, Michelle Simões; Gozzo, Luiz Felippe [UNESP] (Springer Nature, 2021)
In this study, multi-model ensembles are used to understand regional features of future climate trends of cyclones and associated winds in eastern South America. For this, we consider three cyclogenetic hot-spot regions located in south-southeastern Brazil, extreme southern Brazil-Uruguay, and southern Argentina, named, respectively, RG1, RG2 and RG3. The multi-model ensembles consist of four RegCM4 downscalings (RegCM4s) nested in three different global circulation models (GCMs) from CMIP5 under RCP8.5 for the period 1979–2100. ERA-Interim, and CFSR provide the reanalyses ensemble. For the present climate (1979–2005), RegCM4s and GCMs simulate the main characteristics of the cyclone’s genesis and propagation. There is greater agreement between RegCM4s and reanalyses regarding the magnitude and location of stronger winds associated with intense cyclones starting in RG1 and RG2. An important added value is the greater ability of RegCM4s to capture the observed features (phase and amplitude of the annual cycle, intensity, and near surface winds) of cyclogenesis starting in regions away from the boundary domain, such as in RG1 and RG2. In these regions, RegCM4s present smaller (higher) error (correlation) for the frequency of cyclones than GCMs, which improves the representation of cyclones for the whole southwestern South Atlantic domain. RegCM4s are able to simulate in greater agreement with reanalysis than GCMs, the initially stronger cyclones and associated low level winds. For these intense cyclones in the future climate, an intensification of low-level winds off the coast (south-southeast Brazil and south Argentina) and a shift to the south of the upper-level polar jet are projected. Furthermore, there is a clear trend towards decrease in the number of cyclogeneses in each hot-spot region, indicating that each intense cyclone will be associated with stronger low level winds near the eastern South America coast at the end of the twenty-first century.
Keywords: Climate projections; Cyclones; Gcms; RegCM4; South America; Southwestern south Atlantic; Winds